Organic Waste Management into Eco-Enzyme and Maggot Feed at A Hotel in Makassar: A Descriptive Qualitative Study - Amansyah, Munawir; Syarif, Alwiyah Nur; Putri, Resky Ananda; Amalia, Khairiyah Reski; Fadilah, Siti Mutiah; Nurfadila, Nurfadila (Unihealth Community Research, 2026)
Recent hospitality waste studies increasingly promote circular organic-waste treatment, yet empirical descriptions of how hotels operationalize low-cost bioconversion pathways (eco-enzyme fermentation and black soldier fly/maggot production) in day-to-day routines remain limited, particularly in Eastern Indonesia. This study aimed to describe the management of hotel organic waste into eco-enzyme and maggot feed at Mercure Makassar (Makassar City, Indonesia) using a descriptive qualitative design. Data were collected through non-participant observations of kitchen waste flows, in-depth interviews with key hotel personnel (food production, stewarding, housekeeping, engineering, and management), and document review (SOPs, training materials, and relevant local/national regulations). Data were analyzed thematically with iterative coding and triangulation across sources. The findings indicate that the system hinges on (i) source segregation at food-preparation and post-consumption points, (ii) stabilization steps to reduce contamination and odor before processing, (iii) standardized eco-enzyme fermentation using organic residues with sugar/molasses and water ratios commonly reported in the literature (e.g., 1:3:10 or 10:3:1 by weight/volume) and a multi-month maturation period, and (iv) BSF-based bioconversion that rapidly reduces restaurant waste while producing larval biomass and frass as by-products. Implementation is shaped by staff literacy, space constraints, pest-control requirements, and alignment with municipal and national waste-management mandates. Overall, this case demonstrates a feasible, practice-oriented circular pathway for hotels, with implications for SOP development, staff training, and measurable reduction of landfill-bound organic waste in Makassar.